Pesantren sebagai situs kewarganegaraan dan pembentukan budaya kewargaan di Madura - Muwafiq, Ahmad; Samsuri, Samsuri (Universitas Negeri Yogyakarta, 2017)
This research aimed to analyze the pesantren as a site of citizenship and its role in shaping civic culture in Madura. This research was qualitative with a case study The results of this study indicate that: 1) Pesantren as a site of citizenship was a place of sowing identity and spirit of religion and nationality for citizens who are participative, active, caring, sensitive and responsible. 2) The role of pesantren as a site of citizenship in shaping civic culture in Madura, appears in the field of education, social, and politics through the inculcation of religious and national values, community empowerment, and political involvement. All of that were voiced on the religious values that characterize pesantren as an institution of Islamic education. Pesantren with traditional managerial patterns was guided by an open and moderate religious understanding. In the pesantren with modern managerial patterns, the programs were based on Islami, Tarbawi, Ma'hadi, and Indonesiawi. The forms of overcoming the problem were the empowerment of alumni and cooperation with the community.